Creativity and Innovation: State of the Art and Future Perspectives for Research - Brem, Alexander; Puente-Diaz, Rogelio; Agogue, Marine (International Journal of Innovation Management, 2016)
Creativity is a vibrant field of scientific research with important applied implications for the management of innovation. In this article, we argue that the proliferation of creativity research has led to positive and less positive outcomes and discuss five relevant research themes. We first introduce our readers to the different proposed dimensions of a creative object. Next, we explain recent developments on the level of the creativity magnitude issue. Based on that, we review how researchers currently operationalize creativity. After discussing how creativity is conceptualized and operationalized, we outline how it might be enhanced. Finally, we present an overview of the wide variety of methodological approaches currently used in creativity research. We close by calling for more interdisciplinary research and offering other suggestions for future directions.